2020
DOI: 10.1002/anie.202005332
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐Tyr‐1‐carboxylate Mononuclear Iron Center Forms the Active Site of a Paracoccus Dimethylformamidase

Abstract: N,N‐dimethyl formamide (DMF) is an extensively used organic solvent but is also a potent pollutant. Certain bacterial species from genera such as Paracoccus, Pseudomonas, and Alcaligenes have evolved to use DMF as a sole carbon and nitrogen source for growth via degradation by a dimethylformamidase (DMFase). We show that DMFase from Paracoccus sp. strain DMF is a halophilic and thermostable enzyme comprising a multimeric complex of the α2β2 or (α2β2)2 type. One of the three domains of the large subunit and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…To discard the possibility that the MVM capsid might be an unusual complex for which those limiting factors had no significant effect on dynamics-related parameters, we tested the same approach for other viral and cellular protein complexes from the PDB (Berman et al, 2000) and EMDB (Lawson et al, 2016) repositories. Four different assemblies solved to atomic or near atomic resolution by both X-ray crystallography and cryo-EM were selected: β-galactosidase (Bartesaghi et al, 2018; Juers et al, 2000), dimethylformamidase [DMFase, (Arya et al, 2020; Vinothkumar, Arya, Ramanathan, & Subramanian, 2021)], apoferritin (Masuda, Goto, Yoshihara, & Mikami, 2010; Yip, Fischer, Paknia, Chari, & Stark, 2020) and porcine circovirus-2 [PCV-2, (Liu, Guo, Wang, Li, & Jiang, 2016; Mo et al, 2019)]. For every macromolecular complex a clear correlation between LR values and relative B-factors was found (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To discard the possibility that the MVM capsid might be an unusual complex for which those limiting factors had no significant effect on dynamics-related parameters, we tested the same approach for other viral and cellular protein complexes from the PDB (Berman et al, 2000) and EMDB (Lawson et al, 2016) repositories. Four different assemblies solved to atomic or near atomic resolution by both X-ray crystallography and cryo-EM were selected: β-galactosidase (Bartesaghi et al, 2018; Juers et al, 2000), dimethylformamidase [DMFase, (Arya et al, 2020; Vinothkumar, Arya, Ramanathan, & Subramanian, 2021)], apoferritin (Masuda, Goto, Yoshihara, & Mikami, 2010; Yip, Fischer, Paknia, Chari, & Stark, 2020) and porcine circovirus-2 [PCV-2, (Liu, Guo, Wang, Li, & Jiang, 2016; Mo et al, 2019)]. For every macromolecular complex a clear correlation between LR values and relative B-factors was found (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…KUFA-1 and Paracoccus sp. strain DMF have the same length as each other and 99% identical residues, and require not only the large subunit but also another small subunit for their activity (Hasegawa et al, 1999;Arya et al, 2020). From structural studies using cryo-EM and crystallography, it was revealed that the DMFase derived from Paracoccus sp.…”
Section: Introductionmentioning
confidence: 99%
“…From structural studies using cryo-EM and crystallography, it was revealed that the DMFase derived from Paracoccus sp. strain DMF (parDMFase) forms an () 2 heterotetramer composed of two large 84 kDa subunits and two small 16 kDa subunits (PDB entry 6lvv; Arya et al, 2020). Although the function of the small subunit remains unclear, it is most likely to play a role in structural stabilization of an enzymatically active form (Arya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450 enzymes (P450s) are a superfamily of heme proteins involved in drug metabolism, xenobiotic detoxification, and steroid biosynthesis [ 1 , 2 ]. P450s are promising biocatalysts for organic synthesis, drug discovery, and bioremediation because of their versatile catalytic oxyfunctionalizations of a variety of substrates [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, one of the limitations of applying P450s as in vitro biocatalysts is that most P450s require reduced nicotinamide cofactors NAD(P)H and a complex system of electron transport partners (redox partners) to activate molecular oxygen for the formation of active species.…”
Section: Introductionmentioning
confidence: 99%